Soviet Russians under Nazi occupation : fragile loyalties in World War II - Enstad, Johannes Due 1983- (New studies in European history, 2018)
Life in the 1930s and the limits of Stalinist civilization -- Hopes and fears: popular responses to the invasion -- Facing annihilation -- The ghost of hunger -- "More meat, milk, and bread than in the Stalinist kolkhoz": life in the de-collectivized village -- Religious revival and the Pskov Orthodox mission -- Relating to German and Soviet power -- Hopes and fears, revisited: the end and aftermath of occupation -- Conclusion